Print‐and‐Grow within a Novel Support Material for 3D Bioprinting and Post‐Printing Tissue Growth. Issue 34 (19th October 2022) - Machour, Majd; Hen, Noy; Goldfracht, Idit; Safina, Dina; Davidovich‐Pinhas, Maya; Bianco‐Peled, Havazelet; Levenberg, Shulamit
Abstract: 3D bioprinting holds great promise for tissue engineering, with extrusion bioprinting in suspended hydrogels becoming the leading bioprinting technique in recent years. In this method, living cells are incorporated within bioinks, extruded layer by layer into a granular support material followed by gelation of the bioink through diverse cross‐linking mechanisms. This approach offers high fidelity and precise fabrication of complex structures mimicking living tissue properties. However, the transition of cell mass mixed with the bioink into functional native‐like tissue requires post‐printing cultivation in vitro. An often‐overlooked drawback of 3D bioprinting is the nonuniform shrinkage and deformation of printed constructs during the post‐printing tissue maturation period, leading to highly variable engineered constructs with unpredictable size and shape. This limitation poses a challenge for the technology to meet applicative requirements. A novel technology of "print‐and‐grow, " involving 3D bioprinting and subsequent cultivation in κ ‐Carrageenan‐based microgels (CarGrow) for days is presented. CarGrow enhances the long‐term structural stability of the printed objects by providing mechanical support. Moreover, this technology provides a possibility for live imaging to monitor tissue maturation. The "print‐and‐grow" method demonstrates accurate bioprinting with high tissue viability and functionality while preserving the construct's shape and size. Abstract : A new printing support material (CarGrow) composed of κ ‐Carrageenan microgels is developed for the long‐term cultivation of 3D printing cellular scaffolds. The cultivation of cellular constructs within CarGrow provides a favorable cell environment that minimizes the contraction phenomena of low viscosity hydrogels combined with cells while allowing for live‐cell imaging.